Production of English connected speech processes: an assessment of Cantonese ESL learners' difficulties obtaining native-like speech. Issue 5 (3rd September 2021) - Wong, Simpson W. L.; Dealey, Jessica; Leung, Vina W. H.; Mok, Peggy P. K.
ABSTRACT: Despite English being a core and compulsory part of the curriculum for Chinese English-as-a-second-language (ESL) learners, it is nevertheless often highly challenging for them. This is partly due to the discrepancies between English's citation and spoken form and the lack of recognition this pronunciation receives within ESL classrooms. With this in mind, the current study focuses on a highly significant, yet understudied, feature of fluent English speech: connected speech phonological processes (CSPPs). Through analysing the oral recordings of 60 Cantonese ESL university students, the foundation of non-native-like English CSPP productions is examined. Results of error analysis highlight the multitude of interrelated sources of non-native-like productions and provide support for previously stipulated causes of non-native-likeness, e.g. L1/L2 phoneme inventory gaps, as well as previously unidentified influences, e.g. hypercorrection. The study presents invaluable data and implications regarding the successful assessment, teaching, and learning, of English CSPPs and ultimately fluent connected English speech. (151 words)